Eugene Onegin - Fisher, Burton D. (Opera Journeys, 2000)
A comprehensive opera-guide, featuring Principal Characters in the Opera, Brief Story Synopsis, Story Narrative with Music Highlight Examples, and Burton D. Fisher's insightful and in depth Commentary and Analysis.
"Russian opera in three acts, music by Peter Ilyich Tchaikovsky; libretto by Tchaikovsky and Konstantin Shilovsky after the poem Eugene Onegin by Alexander Pushkin."
Keywords: Tchaikovsky, Peter Ilich, -- 1840-1893. -- Evgeniĭ Onegin.; Tchaikovsky, Peter Ilich, -- 1840-1893. -- Evgeniĭ Onegin -- Criticism and interpretation.; Evgeniĭ Onegin (Tchaikovsky, Peter Ilich); Operas -- Stories, plots, etc.; MUSIC -- Genres & Styles -- Opera.; Operas; Criticism, interpretation, etc.; Stories, plots, etc.